1996
DOI: 10.1007/s00282-996-0313-4
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase inhibitors (CKIs) and hematological malignancies

Abstract: Cell proliferation control is ensured by a group of proteins named cyclin-dependent kinases (CDKs), the activation of which is dependent on phosphorylation and cyclin association. In parallel, these CDKs are negatively controlled by two distinct groups of inhibitory proteins, the cyclin-dependent kinase inhibitors (CKIs). The first group, including p16Ink4a, p15Ink4b, p18Ink4c and p19Ink4d, is specific for the G1 CDKs, CDK4 and CDK6, inhibiting the kinase activity of cyclin D/CDK4-CDK6 complexes on pRb. p16Ink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…Increasing p21 CIP1 = WAF1 expression could affect the phosphorylation of CDK4. The blocking at G 1 from entry into the S-phase appears to be mediated by the downregulation of the CDK4-associated kinase activity in association with the induction of p21 CIP1 = WAF1 [13,14]. With combined treatment in our experiment, the expression levels of cyclin D1 and CDK4 were lower when compared with either treatment alone.…”
Section: Discussioncontrasting
confidence: 52%
“…Increasing p21 CIP1 = WAF1 expression could affect the phosphorylation of CDK4. The blocking at G 1 from entry into the S-phase appears to be mediated by the downregulation of the CDK4-associated kinase activity in association with the induction of p21 CIP1 = WAF1 [13,14]. With combined treatment in our experiment, the expression levels of cyclin D1 and CDK4 were lower when compared with either treatment alone.…”
Section: Discussioncontrasting
confidence: 52%
“…Rapid Induction of p21 WAF1 by DNA MeTase InhibitionAnother member of the cyclin-dependent kinase inhibitor (CDKI) family p21 WAF1 , inhibits a wide range of cyclin⅐CDK complexes involved in G 1 and S phase progression (43)(44)(45). Recently it has been observed that an inverse correlation exists between p21 WAF1 and DNA MeTase protein levels in SV40-transformed and nontransformed cells (46).…”
Section: Reactivation Of P16 Ink4a By Mg88 Causes Accumulation Of Hypmentioning
confidence: 99%
“…The reduction in the activity of CDK4, 6 and 2 by SAD in HEPM cell cultures ( in vitro ) and of CDK 2 in vivo can also be a consequence of SAD‐induced increase in the levels of the CDK inhibitors including p21 and p57 in vitro and possibly p21 in vivo. Increased levels of p21 are known to inhibit CDK kinase activity (Baghdassarian and Ffrench, 1996). Another mechanism by which SAD‐induced increase in the p21 level can contribute to the anti‐proliferative activity of SAD is by its binding to PCNA leading to inhibition of its function in DNA replication (Helt and Galloway, 2003).…”
Section: Discussionmentioning
confidence: 99%